2010
DOI: 10.3819/ccbr.2010.50004
|View full text |Cite
|
Sign up to set email alerts
|

Rudiments of mind: Insights through the chick model on number and space cognition in animals.

Abstract: Studies on human infants, focused on the ontogenetic origins of knowledge, have provided evidence for a small set of separable systems of core knowledge dealing with the representation of objects, number, and space. We investigated core knowledge systems from a comparative perspective, making use of the domestic chick as a model system, and filial imprinting as a key to animal mind. Here, we discuss evidence showing precocious abilities in the chick for representing: (i) the cardinal and ordinal/sequential asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 122 publications
(112 reference statements)
2
28
0
1
Order By: Relevance
“…However, research in non‐human species has found evidence for many similar abilities in controlled rearing conditions that do not offer any relevant learning experience (e.g., object permanence in chicks reared without having seen a single instance of object occlusion). These studies lend credence to the conclusion that core knowledge in humans may also be, at least in part, innate (Vallortigara, ; Vallortigara, Regolin, Chiandetti, & Rugani, ).…”
Section: Core Knowledge In Early Cognitionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, research in non‐human species has found evidence for many similar abilities in controlled rearing conditions that do not offer any relevant learning experience (e.g., object permanence in chicks reared without having seen a single instance of object occlusion). These studies lend credence to the conclusion that core knowledge in humans may also be, at least in part, innate (Vallortigara, ; Vallortigara, Regolin, Chiandetti, & Rugani, ).…”
Section: Core Knowledge In Early Cognitionsupporting
confidence: 60%
“…However, research in non-human species has found evidence for many similar abilities in controlled rearing conditions that do not offer any relevant learning experience (e.g., object permanence in chicks reared without having seen a single instance of object occlusion). These studies lend credence to the conclusion that core knowledge in humans may also be, at least in part, innate (Vallortigara, 2012;Vallortigara, Regolin, Chiandetti, & Rugani, 2010). While such evidence has been used to argue that very young infants are equipped with basic expectations about the world, a frequent criticism of the idea of core knowledge is that it denies or ignores the contributions of development and experience.…”
Section: Core Knowledge In Early Cognitionmentioning
confidence: 63%
“…The domestic chick is a precocial species that has been largely used as a model system in ethology and neurobiology for the study of early learning (Andrew, 1991;Rogers, 1996), and recently it has become a focus of interest and insight with respect to several classical issues in developmental psychology, taking advantage in particular of the behavioural techniques made available by filial imprinting (for reviews see Vallortigara, 2004Vallortigara, , 2006Vallortigara, , 2009bVallortigara, Regolin, Chiandetti, & Rugani, 2010). Imprinting is the learning process by which the young of some animals learn the characteristics of an object-usually a social partner-by simply being exposed to it soon after hatching (Bateson, 2000;Horn, 2004).…”
Section: Natural-born Physicistsmentioning
confidence: 99%
“…Recent experiments on newly hatched domestic chicks Vallortigara et al, 2010) enable researchers to appreciate core components of animals' numerical cognition, that is, a set of building block systems that emerge early in ontogeny and show characteristic limits of domain and task specificity (sensu Spelke, 2000). Chicks were reared with five identical objects (small balls).…”
Section: Arithmetic Skillsmentioning
confidence: 99%